2018
DOI: 10.1007/s11162-018-9524-0
|View full text |Cite
|
Sign up to set email alerts
|

How Valid is Grit in the Postsecondary Context? A Construct and Concurrent Validity Analysis

Abstract: College admissions leaders increasingly desire to incorporate non-cognitive factors like grit into admissions decisions. Consequently, we examined the validity of the Short Grit Scale (Grit-S) using data collected on undergraduates attending 38 colleges. Using confirmatory factor analysis (CFA), we found that Grit-S does not possess adequate model fit; however, a modified version of the scale does possess this property. Using multi-group CFA, we also found that Grit-S is relatively invariant across multiple de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 28 publications
9
33
0
Order By: Relevance
“…These investigations revealed that grit is positively correlated with nonacademic outcomes including retention in military programs as well as achievement in the National Spelling Bee competition (e.g., Duckworth et al, 2007;Eskreis-Winkler et al, 2014) and retention in career and married life (Eskreis-Winkler et al, 2014). Besides, grit has shown to be positively associated with academic achievement and certain constructs including classroom management (Banse and Palacios, 2018), teacher's support (Keegan, 2017;Lee and Drajati, 2019;Lee and Hsieh, 2019;Lee, 2020;Yoon et al, 2020), academic achievement (Akos and Kretchmar, 2017), self-efficacy (Usher et al, 2019), engagement (Von Culin et al, 2014;Wolters and Hussain, 2015;Aparicio et al, 2017;Hodge et al, 2017;Fosnacht et al, 2018;Wei et al, 2019), education motivation (Piña-Watson et al, 2015), and achievement goals (Chen et al, 2018).…”
Section: L2 Gritmentioning
confidence: 99%
“…These investigations revealed that grit is positively correlated with nonacademic outcomes including retention in military programs as well as achievement in the National Spelling Bee competition (e.g., Duckworth et al, 2007;Eskreis-Winkler et al, 2014) and retention in career and married life (Eskreis-Winkler et al, 2014). Besides, grit has shown to be positively associated with academic achievement and certain constructs including classroom management (Banse and Palacios, 2018), teacher's support (Keegan, 2017;Lee and Drajati, 2019;Lee and Hsieh, 2019;Lee, 2020;Yoon et al, 2020), academic achievement (Akos and Kretchmar, 2017), self-efficacy (Usher et al, 2019), engagement (Von Culin et al, 2014;Wolters and Hussain, 2015;Aparicio et al, 2017;Hodge et al, 2017;Fosnacht et al, 2018;Wei et al, 2019), education motivation (Piña-Watson et al, 2015), and achievement goals (Chen et al, 2018).…”
Section: L2 Gritmentioning
confidence: 99%
“…The short version of the Grit Scale (Duckworth et al, 2007) has been questioned in some studies. This well-known and widely-used scale was validated with 2 first-order factors (perseverance of effort and consistency of interests) and 1 second-order factor (grit) (Duckworth & Quinn, 2009), though, recent studies have proposed either a unidimensional structure (Areepattamannil & Khine, 2017;González et al, 2019) or a structure with two distinct factors (Abuhassán & Bates, 2017;Datu et al, 2016;Fosnacht et al, 2019;Wolters & Hussain, 2015). Finally, some authors have found low reliability for the Grit-S scale (Clark & Malecki, 2019).…”
Section: Article In Pressmentioning
confidence: 99%
“…In a meta-analysis, Credé et al (2017) find a strong role for perseverance in explaining variation in GPA, but almost no incremental role for grit, after controlling for conscientiousness. Most recently Fosnacht et al (2019) find that the perseverance subscale of grit was positively related to GPA for college students. Caviglia-Harris and Maier (2020) find that grades are positively associated with conscientiousness in early semesters and with grit up until students' final year.…”
Section: Evidence On the Determinants Of Gpamentioning
confidence: 99%
“…Recent work in economics, educational psychology, and higher education have expanded and refined the list of student-based inputs affecting educational attainment and academic success to include the importance of personality characteristics (Schmitt et al 2009 ; Heckman and Kautz 2012 ; Richardson et al 2012 ; Kautz et al 2014 ; Caviglia-Harris and Maier 2020 ; Sweet et al 2019 ; and Martínez et al 2019 ), peers (Berthelon et al 2019 ; Pu et al 2020 ) and student health (Larson et al 2016 ; and Wallis et al 2019 ). Each of these categories of determinants represent a wide literature covering specific cases from practical intelligence (Schmitt et al 2009 ), grit (Fosnacht et al 2019 ), substance abuse (Wallis et al 2019 ), and stress from financial or family difficulties (Larson et al 2016 ).…”
Section: Literaturementioning
confidence: 99%